2012
DOI: 10.1128/jvi.00996-12
|View full text |Cite
|
Sign up to set email alerts
|

Gag-Specific Cellular Immunity Determines In Vitro Viral Inhibition and In Vivo Virologic Control following Simian Immunodeficiency Virus Challenges of Vaccinated Rhesus Monkeys

Abstract: A comprehensive vaccine for human immunodeficiency virus type 1 (HIV-1) would block HIV-1 acquisition as well as durably control viral replication in breakthrough infections. Recent studies have demonstrated that Env is required for a vaccine to protect against acquisition of simian immunodeficiency virus (SIV) in vaccinated rhesus monkeys, but the antigen requirements for virologic control remain unclear. Here, we investigate whether CD8 ؉ T lymphocytes from vaccinated rhesus monkeys mediate viral inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Thus, the modest virologic control likely reflected Env-specific immune responses, although the magnitude and breadth of Env-specific T lymphocyte responses were not clearly correlated with virologic control (Supplementary Table S2). This is consistent with our previous observations that virologic control following challenge is primarily mediated by Gag-specific cellular immune responses (Stephenson et al, 2012a), and thus it is not surprising that the observed virologic control was only modest in this study. In contrast, similar Ad/MVA and Ad/Ad vector regimens expressing SIVsmE543 antigens afforded >2 log reductions of setpoint viral loads following heterologous SIVmac251 challenges (Barouch et al, 2012).…”
Section: Resultssupporting
confidence: 94%
“…Thus, the modest virologic control likely reflected Env-specific immune responses, although the magnitude and breadth of Env-specific T lymphocyte responses were not clearly correlated with virologic control (Supplementary Table S2). This is consistent with our previous observations that virologic control following challenge is primarily mediated by Gag-specific cellular immune responses (Stephenson et al, 2012a), and thus it is not surprising that the observed virologic control was only modest in this study. In contrast, similar Ad/MVA and Ad/Ad vector regimens expressing SIVsmE543 antigens afforded >2 log reductions of setpoint viral loads following heterologous SIVmac251 challenges (Barouch et al, 2012).…”
Section: Resultssupporting
confidence: 94%
“…A significant inhibition of HIV-1 infectivity of PBMCs was found ex vivo postimmunization compared with that preimmunization. Although the infection was assayed ex vivo, there is evidence from studies in rhesus macaques that ex vivo viral inhi- bition is consistent with in vivo viral control following viral challenge of the vaccinated animals (31). HIV tropism is largely generated by coreceptor selection, but initial transmission is commonly by the R5 strain of HIV-1, which utilizes the CCR5 coreceptor (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have evaluated an Ad26 vector-based vaccine for HIV-1 in clinical trials (7, 8), and preclinical studies with Ad26-based vaccine regimens in non-human primates resulted in partial protection against acquisition of infection as well as virologic control following SIV mac251 challenges (911). Virologic control correlated with vaccine-elicited SIV-specific CD8 + T cell responses (912). However, relatively little is known about the CD4 + T cell requirement to generate CD8 + T cell memory responses following vaccination.…”
Section: Introductionmentioning
confidence: 99%